Variáveis relacionadas ao comportamento em fadiga e modo de falha de restaurações CAD/CAM - Velho, Helder Callegaro (2023)
This thesis is composed of 3 studies. Study 1 evaluated the influence of the piston material (glass fiber-reinforced epoxy resin or stainless steel) and the piston tip diameter (6 or 40 mm) on the fatigue mechanical behavior, failure mode, and stress distribution of feldspathic ceramic simplified restorations. The piston diameter showed an influence on the fatigue behavior (the smaller the diameter, the worse fatigue behavior), failure mode, and stress distribution of feldspathic ceramic simplified restorations. However, the influence of piston material is only observed when 6 mm diameter pistons are used (glass fiber-reinforced epoxy resin results in better fatigue behavior than stainless steel). Considering that the 6 mm diameter pistons tend to underestimate fatigue performance, they should be avoided in fatigue testing of simplified feldspathic ceramic restorations with a thickness ≤ 1mm. Study 2 set out to characterize the effect of the occlusal contact region on the mechanical fatigue performance and on the fracture region of monolithic lithium disilicate ceramic crowns. Load application on distinct occlusal contact regions affects the stress distribution pattern and consequently the mechanical fatigue performance and fracture region of the monolithic lithium disilicate ceramic crowns. A combination of loading at distinct regions is recommended to promote better evaluation of the fatigue behavior of a restored set. Study 3 evaluated the effects of cusp inclination of the prosthetic preparation’s occlusal surface on the fatigue behavior, failure mode and stress distribution of glass-ceramic and resin composite occlusal veneers. Three different occlusal surface cusp inclination degrees (0°, 15 and 30°) and two type of restorative material (lithium disilicate or resin composite) were considered. Despite different substrate preparation cusp inclination degrees, the restorations were designed maintaining 30° inclination between the cusps at the occlusal surface and a thickness of 0.7mm at the central groove region of the restorations. From a mechanical standpoint, RC occlusal veneers behave better than LD occlusal veneers when the inclinations of the cusps in the prosthetic preparation are 30°. LD occlusal veneers exhibit better mechanical behavior then RC occlusal veneers when the prosthetic preparation cusps have 0° inclinations. When a cusp inclination of 15° is preserved, both restorative materials behave similarly.